Mapeamento de aplicações das ferramentas digitais da indústria 4.0 na cadeia de suprimentos em empresas de máquinas agrícolas - Rosa, Jorge Luiz Amaral (Universidade Federal de São Carlos, 2026)
The agricultural machinery sector is characterized by its importance to the Brazilian economy, generating approximately BRL 72 billion in net revenue in 2023. The supply chain is defined as the connected network from suppliers to the delivery of products and services to the customers. With the advent of technological innovations, there has been an evolution toward the concept of Supply Chain 4.0, an offshoot of Industry 4.0. There was a gap in academic research on the challenges of digital tools implementation in the agricultural machinery sector. Through exploratory research with both qualitative and quantitative approaches, the objective was to map which Industry 4.0 tools are applied in the supply chain in farm machinery companies, in the areas of Logistics, Planning and Procurement. A total of 18 employees of five companies of this sector, located in four Brazilian states - São Paulo, Minas Gerais, Parana and Rio Grande do Sul - were interviewed. Through combination of a systematic literature review and the formulation of open and closed questions, the answers were identified and analyzed to define the challenges and maturity of using digital technologies in Supply Chain area.
Mapping the applications of Industry 4.0 digital tools in the supply chain of agricultural machinery companies.
Keywords: Cadeia de suprimentos; Transformação digital; Máquinas agrícolas; Indústria 4.0; Tecnologias digitais; Supply chain; Digital transformation; Agricultural machinery; Industry 4.0; Digital technologies; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL; 9. Indústria, Inovação e Infraestrutura